The Qur’anic Perspective On Identity Construction In Social Media - Fathorrahman, Fathorrahman; Faizudin, Faizudin; Mubah, Hilmi Qosim; Hossam, Ahmed; Kaya, Cemil (STAI Publisistik Thawalib Jakarta, 2026)
Social media users frequently engage in excessive self-presentation, including ostentation and arrogance, without regard for Islamic values; this leads to digital identities that conflict with religious ethical standards. This study seeks to examine identity construction on social media through a Qur’anic lens and to ascertain the influence of Islamic values on users' digital interactions. This study employs a qualitative approach, beginning with a literature review in Scopus. Subsequent steps involved editing, organizing, and analyzing the content, along with an assessment of the sources' accuracy and relevance to the topic. The results indicate that the process of identity formation on social media is influenced by digital interactions, cultural values, and Islamic ethical guidelines. Muslim adolescents navigate their religious and social identities through their shared content, demonstrating positive values and refraining from arrogant or disparaging conduct. Social media platforms, while facilitating self-expression, religious education, and community engagement, simultaneously present difficulties concerning misinformation and social pressures. Users can cultivate a balanced and responsible digital persona by incorporating Qur’anic tenets, including tabayyun (verification), humility, and honesty. Consequently, the construction of a Muslim digital identity should be congruent with Qur’anic principles, thereby directing online conduct and ethical decision-making. This study contributes to digital ethical awareness, provides direction for Islamic interactions on social media, and supports research into communication and identity.